Biconservative submanifolds in product of space forms - Llamoca, Milagros Anculli (2024)
In this work, we explore some aspects of the theory of biconservative submanifolds. More precisely, we focus on certain biconservative submanifolds in product spaces and study their relationship with a special class of submanifolds, named class A . Moreover, motivated by the classification of biconservative surfaces in Qn(c) × R with parallel mean curvature vector field, we study the equivalent problem in the context of Lorentz space Q4(c) × R1.